Time dependent efficiency of free trade agreements: the case of Slovenia and the CEFTA agreement - Damijan, Joze P.; Masten, Igor (Economic & Social Studies, 2002)
In international trade literature there is a common feature that the abolishment of barriers to trade leads to direct expansion of trade flows. Many empirical studies that simulate welfare effects of trade liberalisation explicitly make use of this direct tariff reduction ? trade expansion mechanism. On the contrary, this paper explores panel data to analyse the time dependent efficiency of Free Trade Agreements (FTAs). It is shown that trade liberalisation per se needs time to become effective, and that immediately after the enforcement of the FTA the autonomous factors (such as domestic demand for particular import goods) are of great importance. Using an illustrative case of rapid expansion of Slovenian imports from other CEECs in the period 1993?1998, the paper demonstrates that the tariff reductions become effective in the second to third year after enforcement of the FTA. In addition, the relation between tariff reductions and trade expansions is non-linear, which reflects the time needed for new business connections to be established.
Keywords: Time dependent efficiency; Free trade agreements; Slovenia; CEFTA; Tariff reductions; Trade growth